2013
DOI: 10.1111/jace.12234
|View full text |Cite
|
Sign up to set email alerts
|

First‐Principles Study on Site Preference of Aluminum Vacancy and Nitrogen Atoms in γ–Alon

Abstract: The disorder in c-alon is caused by random arrangement of nitrogen atoms and aluminum vacancies. To understand the properties and electronic structure of c-alon by theoretical methods, the most reasonable structure model is needed. We examined the site preference of nitrogen atoms and aluminum vacancies by first-principles density functional theory (DFT) calculations on Al 24 O 24 N 8 and Al 23 O 27 N 5 . The calculated results for Al 24 O 24 N 8 with the lowest total energy indicated that nitrogen atoms prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 46 publications
(62 reference statements)
5
45
0
Order By: Relevance
“…This process leads to various configurations in the structure of γ‐alon. Our latest theoretical work and the previous reports demonstrated that the nitrogen atoms prefer to distribute far away from each other, and the aluminum vacancy prefers coordinating with oxygen atoms at the octahedral site in γ‐alon . The conclusion could guide the construction of supercell models of γ‐alon.…”
Section: Methodssupporting
confidence: 59%
“…This process leads to various configurations in the structure of γ‐alon. Our latest theoretical work and the previous reports demonstrated that the nitrogen atoms prefer to distribute far away from each other, and the aluminum vacancy prefers coordinating with oxygen atoms at the octahedral site in γ‐alon . The conclusion could guide the construction of supercell models of γ‐alon.…”
Section: Methodssupporting
confidence: 59%
“…Thus, the band gap of AlON here is estimated to be 5. AlON is a typical non-stoichiometry compound and crystal defects, such as aluminum vacancies are assumed in the AlON due to the deviation from the "ideal" composition [9][10][11][12][13]. As well known, a stable system requires the minimum potential.…”
Section: Resultsmentioning
confidence: 99%
“…A stable AlON is a non-stoichiometry compound and thus rich of defect structures. Both the theoretical calculation and experimental works evidenced that aluminum vacancies (V Al ′″ ) are predominant in AlON crystal and they are located at the octahedral sites [9][10][11][12][13]. These defects, which may occur during sintering process, will exert remarkable influence on the properties of AlON.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, γ-AlON contains vacancies as regular part of the crystal, which are mainly distributed in the octahedral site. 39,40 When doped with Mn 2+ or rare earths, γ-AlON can be developed into interesting luminescent materials. Xie 41 The Mn 2+ -Mg 2+ co-doped sample yields 1.7 times of the emission intensity of the sample containing only Mn 2+ , and the emission band is red-shifted with the FWHM increasing from 32 to 44 nm (see Fig.…”
Section: β-Sialon:eumentioning
confidence: 99%